Crisis de postulantes s comunicadores en estudios de tercer nivel en la Zona 1 de Ecuador en 2019- 2022 - Changuan Amuy, Darla Micaela (2023)
The present document is a research that arises from the need to know the causes of the decline in the number of applications to communication careers in Zone 1 of Ecuador. Likewise, we are interested in determining the role of the current and future communicator. In this context, issues related to shortcomings in the design of studies, lack of labor supply, dissemination and socialization of the career and labor competencies were observed. The database on the object of study was reviewed through the reading of texts for the construction of the state of the art. The design of the methodology consists of a qualitative approach through the analogical method for which the techniques of interview, focus group and observation were established. The sample consisted of PUCE I students, student representatives, directors and experts in the field of communication 16 and the curricula of the universities that offer a degree in communication. Among the variables applied were study programs, professional practices, costs, dissemination strategies and labor supply. The results obtained show that, in general terms, the degree in Communication is not in crisis and can be accepted by citizens and students if certain changes and parameters are met, including the creation of specialties, improving the curriculum and increasing the number of hours of pre-professional internships.